2018
DOI: 10.1371/journal.pone.0189042
|View full text |Cite
|
Sign up to set email alerts
|

Association of sex hormones with physical, laboratory, and imaging markers of anthropometry in men and women from the general population

Abstract: ObjectivesThe aim of this study was to evaluate the association of sex hormones with anthropometry in a large population-based cohort, with liquid chromatography-mass spectrometry (LCMS)-based sex hormone measurements and imaging markers.Study design/Main outcome measuresCross-sectional data from 957 men and women from the population-based Study of Health in Pomerania (SHIP) were used. Associations of a comprehensive panel of LCMS-measured sex hormones with anthropometric parameters, laboratory, and imaging ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Similar research was conducted by Seyfart T et al [ 30 ], who evaluated the association between sex hormones and anthropometry in a large population-based cohort, and found that testosterone levels were inversely associated with all relevant anthropometric parameters in men. On the other hand, a significant positive relationship between obesity and DHEA-S was demonstrated by Turkish researchers [ 31 ]. Their study, however, involved only 37 men.…”
Section: Discussionmentioning
confidence: 99%
“…Similar research was conducted by Seyfart T et al [ 30 ], who evaluated the association between sex hormones and anthropometry in a large population-based cohort, and found that testosterone levels were inversely associated with all relevant anthropometric parameters in men. On the other hand, a significant positive relationship between obesity and DHEA-S was demonstrated by Turkish researchers [ 31 ]. Their study, however, involved only 37 men.…”
Section: Discussionmentioning
confidence: 99%
“…In opposition to these results a RCT (43) and two observational studies examining changes in body weight in male patients with hypogonadism before and after initiation of testosterone treatment found a mean decrease in BMI of approximately four BMI points (44, 45, 46). For women obesity has been associated with higher levels of estrogens (41, 47) but to our knowledge no studies looking at weight change related to treatment of secondary hypogonadism in women has been published.…”
Section: Discussionmentioning
confidence: 99%
“…Sex steroid hormones are likely involved in the sex-related serum leptin differences observed in the current study [ 38 40 ]. In murine adipocytes, leptin production and secretion were reduced by dihydrotestosterone but increased by 17β-estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ]. Increased leptin production per unit mass of adipose tissue induced by sex steroids may explain the higher serum leptin levels in women [ 38 40 ]. Conversely, sex steroids do not appear to influence resting gas exchange [ 41 ].…”
Section: Discussionmentioning
confidence: 99%